THE USE OF THE DICTATION METHOD TO IMPROVE HIGH SCHOOL STUDENTS’ ABILITY TO WRITE AND READ HIRAGANA LETTERS - Siprianus Sanggale; Franky R. Najoan; Marly C.A. Masoko (Faculty of Language and Arts (Fakultas Bahasa dan Seni) Universitas Negeri Manado, 2022)
The purpose of this study is to determine the ability of students in writing and reading Hiragana letters before the use of the dictation method. In addition, to determine the improvement of students' ability to write and read Hiragana letters after the use of the dictation method. The ability to capture and accurately receive what is said or dictated by the teacher, both in writing and spelling, is called the dictation method. This study used a pre-experimental design with a pre-test and post-test group model. The samples in this study were students of class XI MIPA 1 of SMA Katolik Karitas Tomohon. The instrument used was a test. In this study, it was found that there were differences in the results of processed data, namely the pre-test score of 33, 07 and post-test 96.54 and gain 63.47. After that, the pre-test and post-test results were tested using t-test and resulted in a t-count value of 31.90. Therefore, it can be concluded that the ability to write and read Hiragana letters increased after being treated with the dictation method.